Effectiveness of Kuit Lime Leaf Extract and Gelinggang Leaf Extract as Control of the Nephotettix virescens - Ananda, Rena Rizki; Alfitra, Muhammad Arya; Puspitasari, Sahtia Dewi; Mardiana, Gina; Rahmatullah, Rizqy; Irianti, Riya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The green planthopper (Nephotettix virescens) is a major pest that significantly disrupts rice production by transmitting grassy stunt and empty grain viruses. This research aims to develop an effective botanical pesticide from Kuit lime (Citrus amblycarpa) and Gelinggang (Cassia alata) leaf extracts to control green planthopper populations. The study employed an experimental method with three treatment groups: Kuit lime leaf extract, Gelinggang leaf extract, and a combination of both, alongside a chemical pesticide as the control. Mortality rates of green planthoppers were recorded and analyzed. The results showed that the combined extract had the highest efficacy with a mortality rate of 97.5%, followed by Gelinggang extract (85%), and Kuit lime extract (82.5%). The chemical pesticide achieved 100% mortality. The study concludes that the combined extract of Kuit lime and Gelinggang leaves is a highly effective botanical pesticide against N. virescens. This finding supports the use of environmentally friendly plant-based insecticides as a sustainable alternative to synthetic pesticides. Further research is recommended to explore field-scale application and long-term effects on non-target organisms.